2017
DOI: 10.4317/jced.54009
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Root Fracture with Cone Beam Computed Tomography (CBCT): An Epidemiological Study

Abstract: BackgroundThe aim of this study was evaluation of the cone-beam computed tomography (CBCT) image of 50 patients at the ages of 8-15 suspecting root fracture and root fracture occurred, exposed to dental traumatic. In additionally, this study was showed effect of crown fracture on root fracture healing.Material and MethodsAll of the individuals included in the study were obtained images with the cone-beam computed tomography range of 0,3 voxel and 8.9 seconds.(i-CAT®, Model 17-19, Imaging SciencesInternational,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
9
1
2
Order By: Relevance
“…In vivo studies of 3D imaging in paediatric trauma are very rare; for that reason, we included some in vitro and adult studies, although the exclusion criteria were set for these studies. This review suggested that CBCT is more accurate to assess vertical root fractures than 2D imaging, which is also in accordance with the included studies (25–27,66). Despite the advantages, a CBCT scan exposes the patient with additional radiation; hence, it should only be reserved for suspected root fractures diagnosed initially by clinical signs and 2D radiographs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In vivo studies of 3D imaging in paediatric trauma are very rare; for that reason, we included some in vitro and adult studies, although the exclusion criteria were set for these studies. This review suggested that CBCT is more accurate to assess vertical root fractures than 2D imaging, which is also in accordance with the included studies (25–27,66). Despite the advantages, a CBCT scan exposes the patient with additional radiation; hence, it should only be reserved for suspected root fractures diagnosed initially by clinical signs and 2D radiographs.…”
Section: Discussionsupporting
confidence: 81%
“…According to Doğan et al . (25), root fractures are easily overseen on 2D radiographs, due to the direction of the X-ray beam. Evaluation of root fractures should be done by several periapical radiographs at different angles.…”
Section: Resultsmentioning
confidence: 99%
“…Crown root fractures. Cone beam computed tomography permits a more accurate visualization of the course of the often oblique nature of these fractures and the relationship of the fracture to the pulp, periodontium and crestal bone, thus facilitating management (Martos et al 2017, Do gan et al 2018.…”
Section: Use Of Cbct To Assess Tdimentioning
confidence: 99%
“…Three factors are important to classify root fractures: origin, location, and pattern ( 4 ). In their study with cone beam computed tomography (CBCT), Doğan et al ( 5 ) found that the additional presence of crown fractures has a negative effect on the spontaneous healing of root fractures. Most teeth extracted due to root fracture were teeth with prosthetic restorations after root canal treatment and dental fillings ( 6 ).…”
Section: Introductionmentioning
confidence: 99%